Energy efficiency monitoring and economic analysis for energy saving potential in UNITEN - Khan M.R.B.; Jidin R.; Pasupuleti J.; Yew K.C.; Shaaya S.A. (Institute of Physics Publishing, 2023)
This paper discusses on energy efficiency survey for typical buildings in Universiti Tenaga Nasional (UNITEN). Undeniably, wastage of energy will cause the increase of operation cost and depletion of fossil fuel resources which contributes to the climate change issue in the world. UNITEN was commenced in the late 1990s and most of the buildings in this university are not equipped with energy management system. Such system is the solution to reduce energy use while maximizing the comfort levels of the occupants. Disregard to the energy management system, the implementation of other energy saving measures is the main objective of this paper. By taking the right measures, the energy wastage in the buildings of this university can be reduced. Published under licence by IOP Publishing Ltd.